Ethnicity and Housing Status in Nepal - Gautam, Tika Ram (Samsad Journal संसद जर्नल, 2026)
This paper examines the relationship between ethnicity and housing status in Nepal, focusing on household occupancy status and roofing materials as an indicators of social and economic inequality. It utilizes national-level survey data from the Nepal Living Standard Survey (NLSS-IV-2022/23), which includes 46,870 individuals from 9,600 households of Nepal. The findings show significant disparities in housing conditions across caste and ethnic groups. While a majority of households (78.4%) live exclusively in their own dwellings, this rate varies notably by ethnic group: Hill Dalits and Madhesh/Tarai Dalits show higher exclusive occupancy, while Hill Caste group's exhibit more shared living arrangements. Similarly, the type of roofing material used-ranging from durable materials like concrete and galvanized iron to traditional thatch-also differs significantly across ethnic lines. Dalit communities, particularly in the Madhesh/Tarai region, are more likely to reside in homes with low cost, less durable roofing, reflecting deeper structural inequalities. Statistical analysis using Chi-square tests confirms that these differences are not random but strongly associated with ethnicity (p < 0.001). These patterns underscore the role of broader socio-economic, cultural, and geographic factors-including access to resources, urbanization, and marginalization-in shaping housing conditions.